2014
DOI: 10.1103/physrevd.90.044001
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the angular momentum distribution in core-collapse supernova progenitors with gravitational waves

Abstract: The late collapse, core bounce, and the early postbounce phase of rotating core collapse leads to a characteristic gravitational wave (GW) signal. The precise shape of the signal is governed by the interplay of gravity, rotation, nuclear equation of state (EOS), and electron capture during collapse. We explore the detailed dependence of the signal on total angular momentum and its distribution in the progenitor core by means of a large set of axisymmetric general-relativistic hydrodynamics core collapse simula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
137
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(150 citation statements)
references
References 105 publications
12
137
0
Order By: Relevance
“…Due to this, convection is inhibited in these regions, and the GW signature of turbulent convection characteristic of non-rotating core collapse is not present. For slowly rotating core collapse, prompt convection may contribute to the GW signal on timescales of tens of ms [48,54]. Typically, the peak GW strain from rotating core collapse is ∼ 10 −21 − 10 −20 for a source at 10 kpc, and emitted energy in GWs (E GW ) is ∼ 10 −10 − 10 −8 M .…”
Section: A Magnetorotational Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this, convection is inhibited in these regions, and the GW signature of turbulent convection characteristic of non-rotating core collapse is not present. For slowly rotating core collapse, prompt convection may contribute to the GW signal on timescales of tens of ms [48,54]. Typically, the peak GW strain from rotating core collapse is ∼ 10 −21 − 10 −20 for a source at 10 kpc, and emitted energy in GWs (E GW ) is ∼ 10 −10 − 10 −8 M .…”
Section: A Magnetorotational Mechanismmentioning
confidence: 99%
“…• Abdikamalov et al [54] performed axisymmetric general-relativistic hydrodynamics simulations. A 15 M progenitor star was used, and the LattimerSwesty EOS with K = 220 MeV employed [57].…”
Section: Gw Waveform Catalogsmentioning
confidence: 99%
“…There are significant uncertainties in these and it is difficult to exactly predict the time series of the GW signal. Nevertheless, work by several authors [11,16,20,[149][150][151][152] has demonstrated that GW emission from rotating core collapse and bounce has robust features that can be identified and used to infer properties of the progenitor core.…”
Section: Gravitational Waves From Rotating Core Collapse and Bouncementioning
confidence: 99%
“…Such asymmetric dynamics are expected to be present in the pre-explosion stalledshock phase of CCSNe and may be crucial to the CCSN explosion mechanism (see, e.g., [14][15][16][17]). GWs can serve as probes of the magnitude and character of these asymmetries and thus may help in constraining the CCSN mechanism [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Early analytic and semi-analytic estimates of the GW signature of stellar collapse and CCSNe (e.g., [22][23][24][25][26]) gave optimistic signal strengths, suggesting that first-generation laser interferometer detectors could detect GWs from CCSNe in the Virgo cluster (at distances D 10 Mpc). Modern detailed multi-dimensional CCSN simulations (see, e.g., [20,[27][28][29][30][31][32][33][34][35] and the reviews in [36][37][38]) find GW signals of short duration ( 1 s) and emission frequencies in the most sensitive ∼10 − 2000 Hz band of ground based laser interferometer detectors. Predicted total emitted GW energies are in the range 10 −12 − 10 −8 M c 2 for emission mechanisms and progenitor parameters that are presently deemed realistic.…”
Section: Introductionmentioning
confidence: 99%